Fungal composition of environmental aerosols in barnyards - Lanza, Natalia Soledad (2018)
The aim of this work was to evaluate the fungus present in horse corrals, using simple sedimentation as a sampling method. This was done at the end of winter collecting 20 samples from the perimeter of corrals. Samples were obtained by placing Petri dishes with Saboureaud agar 2% glucose supplemented with 0.05% penicillin open at 58 and 113 cm from the ground. The most representative genus in the two sampled levels were Cladosporium sp and Sepedonium sp. It was also identified genus of clinical importance in equines such as Aspergillus, environmental opportunist able to colonize the paranasal sinuses and guttural bags of horses and produce rhinopharyngitis, sinusitis and fungal guturitis.